Congenital primitive neuroectodermal tumour presenting as obstructed labour. Issue 3 (1st May 1998) - Inwald, David; Kempley, Steve; Hird, Michael
Abstract : Brain tumours presenting at delivery are extremely rare. A case of primitive neuroectodermal tumour (PNET) that presented intrapartum with failure to progress due to hydrocephalus is reported. Diagnosis required imaging with magnetic resonance and computed tomography in addition to open biopsy.